Are salivary amylase and pH – Prognostic indicators of cancers? - Atmakuri Shanmukha Ramya; Divya Uppala; Sumit Majumdar; Ch. Surekha; K.G.K. Deepak (Journal of Oral Biology and Craniofacial Research)
Background: Saliva, “Mirror of body's health” has long been of particular interest as a substitute for blood for disease diagnosis and monitoring. The radiation effects on salivary glands are of particular interest in which salivary amylase is a good indicator of salivary glands function. Thus, estimation of these parameters represents a reasonable approach in evaluation of patient's risk for disease occurrence, intensity and prognosis. Aim of study: To evaluate and compare the pH and amylase levels in saliva of cancer patients prior to treatment, patients during treatment. Materials and methods: Saliva samples of 90 individuals were taken which were divided into 3 groups - 30 individuals without cancer, 30 cancer patients prior treatment and 30 cancer patients during treatment. Materials used were pH strips and pH meter, Salivary Amylase assay. Results: Statistical analysis – ANOVA with post-hoc Tukey's test.1) Significant decrease in salivary amylase levels – in cancer patients, during treatment when compared to others.2) Significant decrease in salivary pH levels in newly diagnosed cancer patients prior to treatment. Conclusion: To conclude, pH strips and pH meter showed to be a useful tool in the measurement of pH of saliva in individuals with and without cancer. This study showed that cancer patients without treatment have a lower pH of saliva. Treatment increased the pH of the saliva to a more alkaline level whereas amylase levels decreased in those subjects. Therefore those parameters can be an area of further research with an increased sample size, which in-turn may help in opening the doors for new dimension in non invasive prognostic markers.